2022
DOI: 10.1186/s12864-022-08512-w
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide investigations reveal the population structure and selection signatures of Nigerian cattle adaptation in the sub-Saharan tropics

Abstract: Background Cattle are considered to be the most desirable livestock by small scale farmers. In Africa, although comprehensive genomic studies have been carried out on cattle, the genetic variations in indigenous cattle from Nigeria have not been fully explored. In this study, genome-wide analysis based on genotyping-by-sequencing (GBS) of 193 Nigerian cattle was used to reveal new insights on the history of West African cattle and their adaptation to the tropical African environment, particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…However, it should be emphasized that indels have been given so far less attention in cattle genomic analyses ( Stafuzza et al, 2017 ), despite being part of the important drivers of phenotypic and genetic diversity ( Iqbal et al, 2019 ). Most of the whole genome analyses on African cattle breeds were based on SNPs ( Kim et al, 2017 ; Tijjani et al, 2019 ; Kim et al, 2020 ; Jang et al, 2022 ; Mauki et al, 2022 ; Terefe et al, 2022 ; Terefe et al, 2023 ), while our study is the first to report indels for Ethiopian cattle.…”
Section: Discussionmentioning
confidence: 81%
“…However, it should be emphasized that indels have been given so far less attention in cattle genomic analyses ( Stafuzza et al, 2017 ), despite being part of the important drivers of phenotypic and genetic diversity ( Iqbal et al, 2019 ). Most of the whole genome analyses on African cattle breeds were based on SNPs ( Kim et al, 2017 ; Tijjani et al, 2019 ; Kim et al, 2020 ; Jang et al, 2022 ; Mauki et al, 2022 ; Terefe et al, 2022 ; Terefe et al, 2023 ), while our study is the first to report indels for Ethiopian cattle.…”
Section: Discussionmentioning
confidence: 81%
“…To this end, in this study, we used specific-locus amplified fragment (SLAF) sequencing (SLAF-seq) (Zhou and Pan, 2023) techniques to obtain individual DNA information from 130 XBG cattle. The published data for KZ, BS, and XBH cattle from 48 WGS analyses were downloaded from NCBI and combined with the SLAF-seq data of 129 XBG cattle for joint analysis; the proven feasibility of merging two types of data has previously confirmed the findings of an exploration of olive diversity in plants (Friel et al, 2021) and an assessment of the adaptation of Nigerian cattle in animals (Mauki et al, 2022). This study focused on analyzing the genetic structure, genetic diversity, and selection signatures of the XBG population and aimed to establish a molecular basis that could assist in the conservation, scientific introduction, and selection of breeding resources for Xinjiang Brown cattle.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 8000-10,000 years BC, the Taurine (Bos taurus taurus) and Indicine (Bos taurus indicus) cattle were domesticated from wild aurochs (Bos primigenius) in the Middle East and Indian subcontinent, respectively (Saravanan et al, 2021). In Africa, the earliest group of cattle known to have migrated into the continent were the Bos taurus taurus circa 7,000-4,000 years before present (YBP) and later the Bos taurus indicus circa 4,000-2,000 YBP from their domestication centers (Kim et al, 2020;Mauki et al, 2022). The autosomal DNA indicated that the Bos indicus and Bos taurus breeds are separated <330,000 YBP and the Bos indicus cattle of Chinese was separated <40,000 YBP from Indian and African sisters (Fig 1A) (Utsunomiya et al, 2019).…”
Section: The Evolutionary History Of Ethiopian Cattlementioning
confidence: 99%